Pepatah Minang “Kato Nan Ampek” melalui Animasi 2D - Muhammad Mufti Huwaidi; Eko Purnomo (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
After the pandemic, there has been many cases where a students acted rudely towards their teachers and seniors because of a low morals. With this reason, the designer is interested in teaching the old proverb from Minangkabau, “kato nan ampek”. Kato nan ampek taught us on how to communicate better to someone older, younger, and the same age as you. Designer obtained data through surveys, interviews, and literature data. Then designer analyze the data with a problem solving method 5W + 1H and the design method 4D model. The results will be an informative animation entitled “Pepatah Minang ‘Kato Nan Ampek’ Melalui Animasi 2D”.